Coexistence of sarcopenia and osteoporosis in patients with heart failure: prevalence and association with functional status. (3rd October 2022) - Numazawa, R; Katano, S; Nagaoka, R; Honma, S; Ohori, K; Kouzu, H; Watanabe, A; Fujito, T; Nishikawa, R; Owada, W; Nagano, N; Koyama, M; et al.
Abstract: Background: Sarcopenia, the loss of muscle mass and function, and osteoporosis, a condition of low bone mass and micro-architectural deterioration of bone, frequently coexist and are associated with low functional status in heart failure (HF) patients. Aims: We aimed to investigate the impact of coexistence of sarcopenia and osteoporosis on functional status in HF patients. Methods: This cross-sectional study was conducted using data from patients who admitted to our institute for the diagnosis and management of HF from 1 November 2015 to 30 April 2021. All patients received the dual-energy X-ray absorptiometry (DEXA) method before discharge. The diagnosis of sarcopenia was made according to the criteria of Asia Working Group for Sarcopenia 2019 recommendation as follows: reduced skeletal muscle mass [appendicular skeletal muscle mass index (ASMI) by DEXA, <7.00 kg/m 2 in males and <5.40 kg/m 2 in females] plus lower muscle strength (handgrip strength, <28 kg in males and <18 kg in females) and/or poor physical performance (gait speed, <1.0 m/s; chair stand test time. ≥12 s; short physical performance battery ≤9 points). In addition, bone mineral densities (BMDs) at the lumbar spine, femoral neck, and total femur were measured by DEXA, and osteoporosis was diagnosed when BMDs at any of the three sites were less than 70% of Young Adult Mean (YAM). Functional status was assessed by the Barthel Index (BI) within three days before discharge, and patients with a BI score of <85 points was defined as having functional dependence (FD). The missing data were imputed using multiple imputation by chained -equations algorithm. Results: Four hundred-thirty eight patients [median age of 74 years (interquartile range, 65–82 years), 37% females] were included in the analyses. Of these, percentage of HF patients with sarcopenia, osteoporosis, and sarcopenia and osteoporosis was 45%, 34%, and 20%, respectively (Figure 1A). The analysis of covariance showed a lower %YAM at any sites in patients with sarcopenia than those without sarcopenia (Figure 1B). When patients were divided into subgroups according to the presence or absence of sarcopenia and osteoporosis, the prevalence of FD was 32%, 34%, and 48% in patients with osteoporosis alone, sarcopenia alone, and sarcopenia and osteoporosis, respectively. Multivariate logistic regression analysis indicated that an increase in adjusted odds ratio (OR) for predicting FD was observed across subgroups in the following order: patients with osteoporosis alone [OR, 1.64; 95% confidence interval (CI), 0.63–4.24; p=0.31], those with sarcopenia alone (OR, 2.44; 95% CI, 1.13–5.25; p=0.02) and those with both conditions (OR, 3.34; 95% CI, 1.52–7.38; p<0.01) (Figure 2). Conclusion: There was considerable overlap between sarcopenia and osteoporosis in HF patients, which appeared to be a risk factor for FD. Funding Acknowledgement: Type of funding sources: None.